On the motion of heated fluid in a magnetic field - Cau, Ta Ngoc (Vietnam Journal of Mechanics, 1988)
In these papers the steady motion of heated conducted fluid in a magnetic field is considered. The theorem of the existence of solution is proved and the conditions of solution uniqueness are indicated.